Caution and Silence: The ICJ’s Dual Architecture to Extraterritorial Human Rights in the Climate Context - Jamali, Hazhar (The Age of Human Rights Journal, 2026)
The International Court of Justice’s 2025 Advisory Opinion on climate change confirmed that States are legally obliged to prevent and mitigate climate harm, yet it avoided clarifying whether human rights obligations apply beyond national borders. Instead of addressing this question explicitly, the Court noted that the scope of human rights treaty law and that of customary law are distinct. This article argues that the Court’s cautious distinction between treaty and custom should be read as an opening rather than an end to the question of extraterritoriality. By noting that the extraterritorial application of human rights treaties depends on the specific jurisdiction clauses of each treaty, while at the same time recognising that customary duties of prevention, due diligence, and cooperation continue to operate irrespective of territorial boundaries, the Court preserved the existing treaty framework but left open a distinct pathway for the further development of extraterritorial obligations through customary international law. This reflects the confines and limits of the Advisory Opinion rather than any substantive conclusion on extraterritoriality, leaving further clarification to future cases.